New academic journals: an international overview of indexing and access models - Rosangela Rodrigues; Cristóbal Urbano; Patrícia Neubert; José Miguel Rodríguez-Gairín; Marta Somoza-Fernández (Information Research: An International Electronic Journal)
Introduction. An international analysis of academic journals newly created in the period from 2011 to 2020 according to type of publisher, place of publication, their relationship with open access, and their indexing in databases. Studies of the issues of concentration of journal publisher ownership, uses of metrics, and access to titles reveal a changing landscape that is nevertheless still dominated by large commercial oligopolies. One notable trend is the creation of new titles in various configurations.